The torso ligand, unmasked? - Stein, D.; Stevens, L.M. (Science's STKE: Signal Transduction Knowledge Environment, 2001)
When a transmembrane receptor protein tyrosine kinase (RTK) is expressed throughout the plasma membrane, yet only a specific handful of them must be activated, what's a ligand to do? During the development of the anterior and posterior termini of the Drosophila embryo, uniformly secreted ligand precursors are activated by proteolysis near the location of the receptors that must be activated. Stein and Stevens discuss the recent publication by Casali and Casanova that describes the mechanism of activation of the Drosophila RTK called Torso. In addition, Casali and Casanova may have identified a physiologically relevant ligand for Torso called Trunk. Proteolytic cleavage of the Trunk precursor can activate Torso-dependent signaling, but the existence of cleaved Trunk has not yet been demonstrated in vivo for Drosophila. Stein and Stevens discuss the ramifications of such a highly regulated process of ligand activation, and also prefer alternative scenarios for Torso activation.